The Effect of e-Worksheets in Eco-Friendly Technology Oriented with Argument Driven Inquiry Model to Improve Students Argumentation Skills - Hasnunidah, Neni; Andriani, Devi; Abdurrahman, Abdurrahman (Jurnal Pendidikan MIPA, 2022)
This study aims to describe the effect of implementing e-worksheets on environmentally friendly technology materials with the Argument-Driven Inquiry (ADI) model in improving students' argumentation skills. This study involved 60 grade IX students in a junior high school in South Lampung, Lampung province. The research design used was a non equivalent pretest-posttest control group design with an experimental class of 30 students and a control class of 30 students. Students in the experimental class get learning assisted by e worksheet with the ADI model, while students in the control class are taught using the Problem Based Learning (PBL) model. The results showed that students who were taught using the e worksheets with the ADI model had a higher N-gain (g=0.61 with medium criteria) than students taught using the PBL model (g=0.17 with low criteria). Furthermore, the effectiveness of learning environmentally friendly technology using the ADI model shows a high category (ES=0.84). This shows that the e-worksheet material on environmentally friendly technology using the ADI model was effective in improving students' argumentation skills. Keywords: e-worksheet, argumentation skills, argument-driven inquiry. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp744-753